Production and characterization of crude and refined oil obtained from tilapia heads under different temperatures (Research, Society and Development, 2020)
The extraction of oil by-products from tilapia processing has been a very interesting way of using solid waste, due to its potential benefits to human health. In this sense, the aim of this study was to extract and refine the Nilotic tilapia oil (Oreochromis niloticus) obtained from the wastes (heads) using three different temperatures (40ºC, 50ºC, and 60ºC). The oils (crude and refined) were chemically characterized from peroxide, saponification, acidity, and iodine indices, and fatty acid profiles, as well as the yield of each treatment was calculated. The results showed that the evaluated temperatures had little influence on oil quality and that the highest significance levels were found when comparing crude and refined oils. However, the use of different temperatures for the extraction of oil from Nilotic tilapia heads can be considered effective, in which the temperature of 60ºC provided a better quality oil, mainly due to the acidity index presented and the amounts of fatty acids.